Constant of Pentagonal Fuzzy Number Matrices (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
The fuzzy set theory has been applied in many fields such as management, engineering, theory of matrices and so on. In this paper, some elementary operations on proposed pentagonal fuzzy numbers are defined. We also have been defined some operations on pentagonal fuzzy matrices. The notion of constant of pentagonal fuzzy matrices is proposed and some properties of constant pentagonal fuzzy matrix are verified. Some of their relevant examples are also included to justify the proposed notions.